2019
DOI: 10.4103/jomfp.jomfp_196_18
|View full text |Cite
|
Sign up to set email alerts
|

Solitary neurofibroma of the palate mimicking mucocele: A rare case report

Abstract: Neurofibroma is a benign, slow-growing, peripheral nerve neoplasm. It presents as a solitary tumor or component of neurofibromatosis (NF) and von Recklinghausen's disease. The occurrence of solitary neurofibromas in the oral cavity is less frequent, and those in the palate are reported in less numbers. This report describes an unusual case of solitary neurofibroma in the hard palate which clinically mimicked a mucocele.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…The aggressive nature makes initial monitoring of patients necessary, clinically presenting as neurofibroma only 11 12…”
Section: Discussionmentioning
confidence: 99%
“…The aggressive nature makes initial monitoring of patients necessary, clinically presenting as neurofibroma only 11 12…”
Section: Discussionmentioning
confidence: 99%
“…Neurofibromas, on the other hand, have spindle-shaped tumor cells that are less cytoplasmic than schwannomas, and their nuclei are small, oval in shape, and do not exhibit a palisade pattern. Because of the fibrous components found between the cells, the tumor cells appear wavy [ 1 , 11 ]. In addition to this arrangement of cells, S-100 protein positivity is a major differentiator between neurofibromas and schwannomas, with neurofibromas being positive for S-100 protein, but at a lower rate than schwannomas [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chaubal et al [ 13 ] and Ohno et al [ 16 ] reported that CD34-positive spindle-shaped cells are found in neurofibromas but not in schwannomas. On histopathology, the myxomatous stroma is seen in neurofibromas, but not in schwannomas [ 11 ]. In addition, schwannomas often have capsules, while neurofibromas do not [ 17 ]; therefore, neurofibromas have been reported to be more likely to recur than schwannomas [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurofibromas são neoplasmas benignos de tecido nervoso não-encapsulados, sendo as neoplasias mais comuns em nervos periféricos. São derivados das células de Schwann, dos fibroblastos perineurais ou de ambos (Martorelli, 2009;Broly, 2019;Sekhar, 2019). Afetam principalmente a pele, mas lesões na cavidade oral não são incomuns e quando estas ocorrem, afetam principalmente a língua, mucosa jugal e mucosa gengival.…”
Section: Introductionunclassified